Pengaruh Risiko Luar Negeri Terhadap Pasar Saham di Indonesia Menggunakan Metode ARDL - Teddy Rianto L. Gaol (Politeknik Caltex Riau, 2023)
This study aims to determine the impact of foreign risk factors (geopolitical risk index, Federal Reserve interest rate policy, the rupiah exchange rate against the dollar, S&P 500 index and world oil prices) on the stock market in Indonesia both in aggregate and by sector. This study used Autoregressive-Distributed Lag (ARDL) to analyze long term and short-term relationship dynamics. Empirical results show heterogenous impact of foreign risk factors on the IHSG and sectoral index. In the short-term geopolitical risk index, Federal Reserve interest rate policy, the rupiah exchange rate against the dollar, S&P 500 index and world oil prices impact stock market in Indonesia. In long term, foreign risk factors have relatively low impact on stock market in Indonesia. Geopolitical risks has positive effect the energy sector. US stock market has long-term impact on financial sector. This research is expected to contribute to the financial literature and policy making